Learning from an AVS in a tertiary centre in Bangladesh: Lateralization of Primary Aldosteronism despite inconclusive imaging (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Primary hyperaldosteronism (PA) is a leading & treatable cause of secondary hypertension, yet many cases remain undiagnosed. Adrenal venous sampling (AVS) is the gold standard for subtype classification of  PA when imaging is inconclusive, yet it remains underutilized due to technical difficulty and limited expertise. We report the first case of AVS performed at any medical college hospital in Bangladesh in a middle-aged woman with resistant hypertension and normal imaging, ultimately diagnosed with PA, supported by an elevated aldosterone–renin ratio (ARR, 184) on screening and confirmed by a saline suppression test. Subtype classification was confirmed by adrenal venous sampling, which demonstrated a significant lateralization index of 4.22 (≥4), consistent with unilateral aldosterone excess.  Reporting early institutional experience facilitates quality improvement and skill development in emerging endocrine centres. [J Assoc Clin Endocrinol Diabetol Bangladesh, July 2026; 5 (2): e89445]